Epidemiology of Knowlesi and other Simian Malarias in Humans in the Betong Division of Sarawak - Liew, Sze Tze (Universiti Malaysia Sarawak, (UNIMAS), 2017)
In Sarawak, Plasmodium knowlesi, which is commonly found in long-tailed and pig-tailed macaques, is the main cause for human malaria infections. Other simian malaria parasites from Southeast Asia that can infect humans are P. inui and P. cynomolgi. To date, epidemiological data on knowlesi malaria in Sarawak has been derived solely from hospitalbased investigations and all of them were symptomatic malaria cases. A longitudinal study was therefore undertaken to determine asymptomatic Plasmodium infections including P. knowlesi and other simian malaria parasites infections in the Betong Division of Sarawak. A total of 555 people were recruited from 8 longhouses, which had individuals recently admitted to Betong Hospital with knowlesi malaria. Blood spots, collected bi-monthly over a period of 21 months, were examined using PCR assays. Pooled and non-pooled nested PCR strategies were used to screen DNA extracted from the blood spots for the presence of Plasmodium DNA. Next, each of the genus-positive DNA samples was screened using species-specific primers for P. falciparum, P. vivax, P. malariae, P. ovale, P. knowlesi, P. cynomolgi and P. inui. A subset of samples was also screened with real time PCR for the presence of P. knowlesi. Nine subjects were positive for malaria DNA by nested PCR -- seven P. knowlesi, one P. vivax and one sample that could only be identified as positive for Plasmodium DNA. For real time PCR, 21 samples were positive for P. knowlesi, including two samples that were positive for P. knowlesi by nested PCR. Only one subject, who was positive for both nested PCR and real time PCR for P. knowlesi, was symptomatic and admitted to Betong Hospital. None of the other PCR-positive subjects were febrile nor did any of them sought any medical treatment. Lastly, cloning and sequencing was only successful for 4 out of the 9 samples, in which phylogenetic analyses of these sequences confirmed that samples from three subjects were infected by P. knowlesi and one sample found to be co-infected by both P. knowlesi and P. coatneyi.